2022
DOI: 10.24875/ciru.21000300
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidad después del trasplante de riñón: resultados a 10 años

Abstract: Objectives: In the past decade, advances in immunological therapy have increased the survival of kidney recipients and their grafts. However, it has not achieved the desired level of improvement. This study aims to reveal the mortality among kidney recipients. Methods: Medical data of the patients, who had undergone kidney transplantation (KT) between November 2010 and December 2020, were retrospectively reviewed. Inclusion criteria were adult kidney recipients, who had died. Exclusion criteria were pediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…In the study conducted by Kainz et al, patients waited five years until the first transplantation (Kainz et al, 2022). In the study of Piskin et al, it was reported that patients waited 6 years (74 months) for organ transplantation (Piskin et al, 2022). In our study, it was observed that the waiting time was lower than in the literature, leastwise.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Kainz et al, patients waited five years until the first transplantation (Kainz et al, 2022). In the study of Piskin et al, it was reported that patients waited 6 years (74 months) for organ transplantation (Piskin et al, 2022). In our study, it was observed that the waiting time was lower than in the literature, leastwise.…”
Section: Discussionmentioning
confidence: 99%
“…По данным исследования T. Piskin и соавт., в первые 2 мес. после трансплантации почки, когда наиболее интенсивно применялась иммуносупрессия, инфекция была единственной первопричиной летальности [9].…”
Section: клиническое наблюдениеunclassified